AGAMA, POLITIK, DAN IDEOLOGI MEDIA ( ANALISIS WACANA KRITIS BERITA KORUPSI PETINGGI PARTAI POLITIK ) - Syahputra, Iswandi; Kunandar, Alip; Iqbal, Fajar (El -Hekam, 2016)
There are three sides of the media business today, such as media content providers, audiences as consumers of content, and advertisers as ‘consumers’ other media users. All three are complementary and influence each other, although in many ways, most audiences are often sacrificed in terms of interest. When an issue arises, the media are often considered a factor called ‘news value’ that will attract audiences to consume and then attract advertisers to enter. At other times, the ideology of media also often affect how the news was created, directed, and then deployed. In the case of reported of corruption cases involving officials of political parties in Indonesia of 2014 election, which is affecting Luthfi Hasan Ishaaq (PKS), Ratu Atut Choisyah (Golkar), and Anas Urbaningrum (Demokrat), two major media in Indonesia, Kompas and Republika presented the news in a different way. It is strongly associated with the ideology of each medium. Media ideology are then distinguish the discourse developed Kompas and Republika in reporting cases of the party officials. Results of analysis using Foucault discourse analysis showed that both the national media show a particular discourse in accordance with ideology, and on the other hand also do marginalization of certain discourses are supposed to be there. For example, the discourse of corruption as an extraordinary crime, it is not displayed, enclosed by political discourse and religious identity of each alleged case of corruption.Keywords: Discourse, Religion Identity, Politics, Media Ideology